Chevolución, Chesucristo: historia de un ícono en dos clichés - Verushka Alvizuri (Caravelle)
This paper proposes two approaches in the iconographic study of Che Guevara. The construction of his iconography and the uses of his memory. The stereotypical image of Che Guevara has two faces: the heroic Marxist warrior and the Christian martyr. The portrait Heroic warrior by Alberto Korda and the pictures of the corpse, by Freddy Alborta were realized in exceptional circumstances which are described by this article using an approach of cultural photographic history. The promotion and/or censure of these images shows several uses of Che memory, as symbol of Cuban revolution, of Liberation Church and souvenir of political tourism in Bolivia.